New records of the pampas cat, leopardus colocola (Molina, 1782) (mammalia, carnivora, felidae), from the Chaco ecoregion raise questions about its status in Argentina - Nanni, Ana Sofía (2020)
Leopardus colocola (Molina, 1782) is a poorly known small felid distributed throughout a large portion of South America, reported as extinct in the Pampas of Argentina, and absent from a large portion of the Argentine Dry Chaco. We compile data from the field and national collections to report new occurrence records of this species from the Dry Chaco of Argentina and update its distribution. We discuss the need of further assessments of the distribution of this species in the light of ongoing land-use changes in the area.